The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s0100-69912013000200011
|View full text |Cite
|
Sign up to set email alerts
|

Cirurgia para controle de danos: estado atual

Abstract: A cirurgia de controle de danos é um conceito amplamente aceito atualmente entre os especialistas em trauma abdominal quando se trata de doentes gravemente traumatizados. Nestes pacientes a morte decorre, na maioria das vezes, da instalação da tríade letal (hipotermia, coagulopatia e acidose) e não da incapacidade de reparar as graves lesões presentes. Nesta revisão, os autores abordam a tríade letal, em suas três fases, e enfatizam as medidas adotadas para preveni-las. Além de discutirem a indicação e o empre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
22

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 42 publications
0
7
0
22
Order By: Relevance
“…showed that simple x-ray of the abdomen should not be required, since it has low specificity and sensitivity, while US has sensitivity of 75 to 90% and specificity of 86 to 100%, but it depends on a qualified operator 1 . Studies with US showed that its sensitivity ranged from 68 to 96%, and specificity, from 46.7 to 95.9%, with PPV between 82.2 and 94% and accuracy from 65.7 to 87% [14][15][16][17] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…showed that simple x-ray of the abdomen should not be required, since it has low specificity and sensitivity, while US has sensitivity of 75 to 90% and specificity of 86 to 100%, but it depends on a qualified operator 1 . Studies with US showed that its sensitivity ranged from 68 to 96%, and specificity, from 46.7 to 95.9%, with PPV between 82.2 and 94% and accuracy from 65.7 to 87% [14][15][16][17] .…”
Section: Resultsmentioning
confidence: 99%
“…Studies showed its sensitivity ranging from 91.2 to 98.5%, specificity from 62.5 to 98%, positive predictive value (PPV) from 92.1 to 98% and accuracy of 90% [16][17][18][19][20] . CT findings consist of appendix lumen dilation, thickening of the wall, presence of fecalites and inflammation 1 . In our sample, 72% of the patients in the study group and 68% of the patients in the control group…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…İntraabdominal basınç artışıyla karakterize abdominal kompartman sendromu (AKS) tedavisi sırasında, karın içi basınç artışının önüne geçmek için açık karın yönetimine geçil-mesi abdominal sepsisli, multitravmalı veya ağır akut pankreatitli hastalardaki en uygun tedavi şekli olmuş-tur (13)(14)(15)(16)(17) . Özellikle son birkaç dekattır ortaya çıkmış olan hasar kontrol cerrahisi gereksinimi olan masif hemorajili, ağır sepsisli, akut mezenterik iskemili hastalarda bağırsakların beslenme durumunu görmek isteği, yapılmış olan anastomozun durumunu takip etme dür-tüsü ya da pürülan özellikte peritoneal mayinin batının defalarca irigasyonuyla dışarı alınması ve bunu takip etme isteği bu yöntemin yeğlenmesine temel teşkil eden düşüncelerdir (18,19) . Geçici batın kapama işlemi yapılmasına karar verilen hastalarda daha başlangıçta bu hastaların batınlarının ne zaman ve nasıl kapatılabi-leceği de düşünülmeye başlanmalıdır.…”
Section: Açik Batin Yöneti̇mi̇unclassified